2019
DOI: 10.1038/s41598-018-35820-7
|View full text |Cite
|
Sign up to set email alerts
|

Retail liver juices enhance the survivability of Campylobacter jejuni and Campylobacter coli at low temperatures

Abstract: The high prevalence of Campylobacter spp. in retail liver products was previously reported and has been linked to several outbreaks of campylobacteriosis. The main objective of this study was to investigate the influence of retail liver juices on the survivability of several strains of C. jejuni and C. coli , which were previously isolated from various retail meats at 4 °C. All tested Campylobacter strains showed higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 79 publications
0
29
0
Order By: Relevance
“…It has to be noted, that stress survival of the microaerobic Campylobacter is one of the major and still enigmatic topics in order to explain the pathogens widespread dissemination. C. jejuni was shown to survive longer in liver juice 45 . Aerotolerant C. jejuni strains were identified 46 but also aerotolerant C. coli isolates were highly prevalent in other studies 47 .…”
Section: Discussionmentioning
confidence: 96%
“…It has to be noted, that stress survival of the microaerobic Campylobacter is one of the major and still enigmatic topics in order to explain the pathogens widespread dissemination. C. jejuni was shown to survive longer in liver juice 45 . Aerotolerant C. jejuni strains were identified 46 but also aerotolerant C. coli isolates were highly prevalent in other studies 47 .…”
Section: Discussionmentioning
confidence: 96%
“…It is complicated to remove biofilms because of the sophisticated biofilm regulatory mechanisms involving many genes (Karki et al, 2019) that underlie biofilm formation (Nobile and Mitchell, 2005;Sakuragi and Kolter, 2007;Arenas and Tommassen, 2017;Shukla et al, 2017). Previous research showed that only nanosized ZnO particles had an antibiofilm effect (Alves et al, 2017), mainly because ZnO nanoparticles are small and have a large specific surface area and high oxidation ability, and their effects against biofilms are attributable to the generation of reactive oxygen species on their surface (Zheng et al, 2014;Setyawati et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is easy to acquire C. jejuni from water, soil, and so on (Teh et al, 2014). It is also puzzling that although planktonic C. jejuni has a weak ability to survive multiple stressors in the environment, it can cause foodborne diarrheal illness (Karki et al, 2019;Kim et al, 2019). Research on C. jejuni infections is rare compared to research on other foodborne pathogens, such as Salmonella and Listeria monocytogenes.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in Figure 3, within an avian host, there is evidence to suggest that biofilms may be important. In the presence of chicken exudate, C. jejuni produces a substantial increase in the amount of formed biofilm as well as enhanced survivability in the presence of liver juices [78,79]. Biofilm formation may play an important role in the intermediate steps between avian reservoirs and infection in humans.…”
Section: The Role Of C Jejuni Biofilmsmentioning
confidence: 99%
“…Evidence shows that many of the factors present in the environment can up-regulate biofilm formation in C. jejuni [45,49]. There is also evidence to suggest that C. jejuni either forms biofilm in the chicken intestinal tract [78,79] or adopts an adherent phenotype within avian hosts [80]. This allows the organism to survive on food preparation surfaces and in food products, water reservoirs, and similar environments until the bacteria reach the human host, whereby biofilms are down-regulated and bacterial cells are able to proliferate and invade the epithelium of the intestine.…”
Section: The Role Of C Jejuni Biofilmsmentioning
confidence: 99%